Development of silk fibroin tissue engineering scaffolds via indirect additive manufacturing for cartilage regeneration - Liu, Jolene Mei Jun (2013)
The development of cartilage tissue scaffolds in both craniofacial and orthopaedic surgeries still remains a great challenge in tissue engineering (TE). The architecture of scaffold constructs is one of the important criteria required for cartilage TE as it meets aesthetics and functional purposes in craniofacial and orthopaedic surgeries respectively. TE has been explored in recent years to create desirable cartilage substitutes so as to circumvent the limitations faced in the usage of autogeneous implants and allografts. TE approaches provide an opportunity to construct tissue scaffolds with geometrical properties and mechanical integrities that are comparable to that of native tissues. A viable TE scaffold should include the presence of adequate morphologies to allow optimal cell attachment and mass transportation of essential nutrients. Moreover, the scaffold should provide sufficient physical support for tissue ingrowth and degrade at a comparable rate with the regenerated tissue. Vast varieties of methodologies have since been developed to produce TE scaffolds addressing connective tissues as well as organs. One of the viable approaches includes additive manufacturing (AM) which allows complete user control over the architecture of the scaffold construct. Commercialised AM systems have been widely explored for TE purposes and a main limitation of the direct AM applications include the difficulty to process naturally-derived biomaterials such as proteins and polysaccharides. High temperature and use of toxic solvents are factors that contribute to the disadvantages of direct AM methods. Conversely, indirect AM techniques allow the use of naturally-derived materials and provide user-defined control through the use of a sacrificial mould. The present study proposed a scaffold fabrication technique which involves the application of solvent-casting (a conventional TE approach) on top of the AM-based inkjet printing technique to yield TE scaffolds with both macro- and micro- architectural features. The formation of macro-channels aims to facilitate cell migration towards the interior of the scaffold while the presence of micro-pores serves as anchorage sites for cell attachment, proliferation and extracellular matrix (ECM) secretion. The main objective of this project is to fabricate silk fibroin (SF) scaffold using an indirect AM approach and investigate the viability of the scaffold for cartilage TE. SF, a poly amino-based biopolymer extracted from the Bombyx Mori cocoons, has been widely used for biomedical applications, owing to its superior biocompatibility and mechanical properties. In this study, SF protein was used in its regenerated form in aqueous state to produce SF foams of varying concentrations for the assessment of its mechanical characteristics and biodegradability. Subsequently, simple empirical models were formulated based on experimental results to provide a good basis for the identification of appropriate SF concentration for specific TE application. The TE potential of SF protein was further verified using permeability theory and biodegradation model. The factors that affect the permeability of SF foams were elucidated, while the biodegradation model enables the identification of erosion mode and the prediction of biodegradation life-time of a specimen. The theories were further verified by in vivo studies on nude mice. From the experimental observations, a suitable SF concentration was chosen and used for the fabrication of TE scaffold. Two processes of inkjet printing were analytically modelled in this work to develop further understanding on the operational mechanics of the AM technique. The impaction of a single droplet on a solid surface was first studied. The dynamics of the droplet impact was modelled using energy conservation principles and equations to determine the maximum spreading ratio of droplet upon impact on a surface. The mechanics of line formation via printing was next being modelled. A thermodynamics approach was used to study the coalescence between two deposited droplets and predict the critical time at which the droplets could no longer merge as a result of cooling effect. The coalescence of droplet and its subsequent spreading were also evaluated to be influenced by the effects of drawback which would result in the formation of discontinued line. Finally, SF TE scaffolds, with both macro- and micro- sized morphologies, were produced using the proposed indirect AM technology with the preservation of the protein’s intrinsic properties and without inducing cytotoxicity. The quantitative results obtained from in vitro cell cultures demonstrated the TE constructs as suitable templates for chondrocyte attachment and proliferation. This observation was verified visually from the histology of the specimens after a prolonged period of cultivation. To further elucidate the TE potential of SF scaffolds, the constructs were implanted into nude mice models. The in vivo work revealed that the SF scaffolds promoted cartilage regeneration. Based on the immunohistochemical analysis, the key cartilage components such as the sulphated glycosaminoglycans (GAGs) and collagen type IIwere observed and vascularization networks were found to permeate within the TE constructs.